Prerequisites for a sauccessful project management information system - Smith, Kenneth F
The use of the Management Information System (MIS) is seen as one way of improving the management in third world countries. This article outlines a recent study of Misapplications in a number of development projects, and summarizes users and observers's perceptions about the utility of such MIS for project management. One relatively successful US AID- assisted MIS project in the Philippines was scrutinized in-depth, while still other MIS applications were surveyed. Twelve variables were also isolated and tested in a attempt to establish some common criteria for successful MIS design and application. The study confirms that while there are really no guarantees for success in using MIS, the prospects for im
Keywords: Project Management Information System; Project Management